2020
DOI: 10.1016/j.bbih.2020.100112
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic function and markers of inflammation in well-controlled HIV

Abstract: Purpose HIV-associated autonomic neuropathy (HIV-AN) is common and may be associated with both sympathetic and parasympathetic dysfunction. Sympathetic nervous system (SNS) dysfunction occurs on a continuum of hyper-to hypo-adrenergic function, and may be a mediator between psychological stress and chronic inflammation. We sought to describe patterns of SNS dysfunction in people living with HIV, and to determine whether SNS dysfunction is associated with markers of systemic inflammation (focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…54 Evidence of persisting changes in both innate and adaptive immunity of people recovered from COVID-19 infection could point to underlying dysregulation of the immune system 55 ; however, other studies have failed to show differences in cytokine profiles between long COVID patients and those who have fully recovered. 56 There is evidence to support chronic states of stress and inflammation triggering autonomic dysfunction, potentially through fluctuations in adrenergic tone, 57 which in turn may perpetuate chronic inflammation through vagal dysfunction and its effects on gastrointestinal function and the microbiome. 58 In the central nervous system (CNS), postmortem neuropathology studies of people deceased from COVID-19 infection have shown evidence of neuroinflammation, microglia activation, hypoxic/ischemic changes, and hemorrhagic or ischemic infarcts.…”
Section: Potential Pathophysiologymentioning
confidence: 99%
“…54 Evidence of persisting changes in both innate and adaptive immunity of people recovered from COVID-19 infection could point to underlying dysregulation of the immune system 55 ; however, other studies have failed to show differences in cytokine profiles between long COVID patients and those who have fully recovered. 56 There is evidence to support chronic states of stress and inflammation triggering autonomic dysfunction, potentially through fluctuations in adrenergic tone, 57 which in turn may perpetuate chronic inflammation through vagal dysfunction and its effects on gastrointestinal function and the microbiome. 58 In the central nervous system (CNS), postmortem neuropathology studies of people deceased from COVID-19 infection have shown evidence of neuroinflammation, microglia activation, hypoxic/ischemic changes, and hemorrhagic or ischemic infarcts.…”
Section: Potential Pathophysiologymentioning
confidence: 99%
“…Catecholamines directly affect the growth and virulence of several species of anaerobes, such as Enterobacteriaceae , in the gut ( 137 , 138 ). More recently, this group demonstrated that higher adrenergic baroreceptor sensitivity, an index of a more hyperadrenergic state, was associated with greater inflammation in PWH ( 139 ). Another study with 4000 PWH from the Strategies for Management of Antiretroviral Therapy study revealed cross-sectional inverse associations between heart rate variability with soluble markers of inflammation and coagulation ( 140 ).…”
Section: Neuroendocrine Signaling and The Microbiome-gut-brain Axismentioning
confidence: 99%
“…HIV-1 infects pDC, macrophages and CD4 + T cells in the splenic white pulp, where HIV-1 replicates and then establishes a reservoir of latent virus within these cells during chronic disease [ 85 , 86 , 87 ]. Neural HIV pathology also includes inflammation-mediated destruction of sympathetic nerves that normally regulate the immune functions of these three cell types [ 11 , 31 , 32 ]. As a result, the spleen is a critical site involved in the progression of HIV-1 infection towards clinical immune deficiency and greater susceptibility of infected individuals to opportunistic disease [ 88 , 89 , 90 , 91 ].…”
Section: Splenic Sympathetic Nerves Influence Hiv-1 Cell Entry and Re...mentioning
confidence: 99%
“…The sympathetic nervous system (SNS) innervates secondary lymphoid organs, and is activated by a variety of stressors, including viral infection [ 9 , 10 ]. Sympathetic dysfunction in HIV-1 infection exists as a continuum of early hyper-to-hypo-adrenergic function with disease progression [ 11 ]. Sympathetic activity is linked to prognostic disease indicators of HIV pathogenesis [ 12 , 13 , 14 , 15 , 16 ], as well as in animal models [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation